Successful Latin American initiatives in biophysics - Morales, Marcelo M. (2014)
The II LAFeBS Congress aimed to promote a closer interaction between Latin American and Iberian Peninsula scientists in their respective fields of research, from structural proteomics to molecular bioenergetics. The speakers at this event reflected the importance and development of Biophysics in Latin American Countries, including Portugal and Spain; with 13 of them being invited to write review articles for this special issue of Biophysical Reviews. We hope that the integration of biophysics and biophysicists in Latin America, together with Portugal and Spain, through LAFeBS and POSLATAM can contribute to the future development of biophysics in these two historical partner regions.